Anthropology in Architectural Heritage: A Required Comprehensive View in Baix Empordà (Spain) - Alcindor, Mónica; Roselló, Oriol (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2016)
Throughout the last decades of the last century, the number of buildings that are now considered part of our cultural heritage has been increasing. This increase reflects the perceptions thatpre-industrial society in which these buildings were built is gone. We stand in front of anonymous buildings which acquire a character of singularity, for both it's rural past memory that we know won't come back and the perception of the draw backs of a hyper-industrialized society that, at the same time, foster a sense of bucolic by gone society. There is an awareness and therefore a more detailed analysis and study of the intervention manners. But a too partial study as usually occurs in the case of architects, in many occasion prevents from perceiving the totality of overall reality in which we move and the invisible connections which are really directing our actions. This inability to perceive the real limitations leads to a homogenization on the constructive solutions which avoid any action prior criteria since the market forces, the values of society and certain disaffection on the architect's guild, boost construction uniformity.